2020
DOI: 10.1007/s00705-020-04800-6
|View full text |Cite
|
Sign up to set email alerts
|

Divergent minute virus of canines strains identified in illegally imported puppies in Italy

Abstract: Minute virus of canines (MVC) belongs to the family Parvoviridae, genus Bocaparvovirus, and has been mainly described during enteritis episodes in young dogs. This study reports the characterization of four divergent MVC strains detected between 2012 and 2018, three of which were from dogs illegally imported into Italy, most probably from Eastern Europe, that cluster together phylogenetically but share low genetic similarity with the fourth MVC from an autochthonous dog and other available MVC sequences. Our d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The genetic picture for CPV-2 in Italy appears to be dictated by both legal and illegal movements of companion animals with human migration and travel at the national and international levels, affecting the spread and evolution of CPV-2. This highlights that the continuous national and international monitoring of CPV-2 may aid the understanding of CPV-2 distribution and the tracking of the introduction of strains from foreign countries, as previously demonstrated for other viruses affecting the dog population [ 33 ]. CPV-2 infection presents some peculiarities such as the endemicity status and the vast use of live attenuated vaccines formulated with different CPV-2 variants that render fundamental matching of the collection and analysis of clinical/anamnestic data with virological ones.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The genetic picture for CPV-2 in Italy appears to be dictated by both legal and illegal movements of companion animals with human migration and travel at the national and international levels, affecting the spread and evolution of CPV-2. This highlights that the continuous national and international monitoring of CPV-2 may aid the understanding of CPV-2 distribution and the tracking of the introduction of strains from foreign countries, as previously demonstrated for other viruses affecting the dog population [ 33 ]. CPV-2 infection presents some peculiarities such as the endemicity status and the vast use of live attenuated vaccines formulated with different CPV-2 variants that render fundamental matching of the collection and analysis of clinical/anamnestic data with virological ones.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, no updated information is available regarding the circulation of CPV-2 variants and their genetic characteristics in Northeast Italy from 2015 onwards. This area of Italy is of particular interest as a point of entry of pet animals from Eastern European countries, via legal or illegal movements [ 32 , 33 ], demonstrated by recent studies on the characterization of pathogens of dogs including canine parvoviruses from East Europe and Far East countries [ 32 , 33 ]. The aim of the present study was to characterize the VP2 of CPV-2 strains identified through the diagnostic activity detected between 2013 and 2019 in Northeast Italy, providing updated information on the circulation and distribution patterns of CPV-2 variants.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, pathogens that can be transmitted among multiple host species pose challenges for disease control [47]. Indeed, the interface between wildlife and domestic animals might allow the transmission of pathogens with a potentially disrupting impact on a naïve population [48][49][50][51][52][53]. This occurrence, so far underestimated, deserves further investigations from both sides of the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonitis, hepatitis, myocarditis and lymphadenitis were described in dogs infected with CnMV [ 60 , 143 , 144 ]. CnMV may cross the placental barrier, resulting in early fetal death, birth defects and neonatal mortality [ 60 , 143 , 145 ].…”
Section: Bocaparvovirusesmentioning
confidence: 99%